Pemberdayaan Masyarakat Desa Korleko Melalui Inovasi Pengolahan Ampas Kelapa Menjadi Tepung Yang Bernilai Tambah - Agustiani, Eka; Endang Astuti; Laila Wardani; Suharyati Pebria Ningsih (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Korleko Village in Labuan Haji District, East Lombok Regency, is the largest coconut-producing area in West Nusa Tenggara, but the utilization of coconut pulp waste is still very limited. This community service activity aims to empower housewives who are members of the Family Welfare Movement (PKK) through training in innovative ways to process coconut pulp into value-added flour. The implementation method includes coordination with village officials, outreach, training and practice in making coconut pulp flour, demonstrations of processed products, and evaluation of activity results. The training was held on February 12, 2025, at the Korleko Village Hall and was attended by 25 participants. The results showed an 80-90% increase in participants' knowledge and skills, where the community was able to produce an average of 350 grams of dry flour from 1 kg of wet coconut pulp and understood how to package and market the product. This activity has proven effective in increasing awareness of household waste management, opening new business opportunities, and strengthening the creative economy based on local potential.